Etiologic Agents of Bacterial Sepsis and Their Antibiotic Susceptibility Patterns among Patients Living with Human Immunodeficiency Virus at Gondar University Teaching Hospital, Northwest Ethiopia - Alebachew, Gelila (Biomed Res Int, 2016)
Background. Bacterial sepsis is a major cause of illness in human immunodeficiency virus infected patients. There is scarce evidence about sepsis among HIV patients in Ethiopia. This study aimed to determine the etiologic agents of bacterial sepsis and their antibiotic susceptibility patterns among HIV infected patients. Methods. A cross-sectional study was carried out from March 1 to May 2, 2013. One hundred patients infected with HIV and suspected of having sepsis were included. Sociodemographic data were collected by interview and blood sample was aseptically collected from study participants. All blood cultures were incubated aerobically at 35°C and inspected daily for 7 days. The positive blood cultures were identified following the standard procedures and antimicrobial susceptibility testing was performed using disk diffusion technique. Data was entered by Epi-info version 3.5.1 and analysis was done using SPSS version 20. Results. Of the study participants, 31 (31%) confirmed bacterial sepsis. The major isolates were 13 (13%) Staphylococcus aureus, 8 (8%) coagulates negative staphylococci, and 3 (3%) viridans streptococci. Majority of the isolates, 25 (80.6%), were multidrug resistant to two or more antimicrobial agents. Conclusions. Bacterial sepsis was a major cause of admission for HIV infected patients predominated by Staphylococcus aureus and coagulase negative staphylococci species and most of the isolates were multidrug resistant.